Determinant of Stress and Burnout among Nurses at the Second Wave of the Indonesian COVID-19 Pandemic: A National Web-based Survey - Sofiani, Yani; Kamil, Abdu Rahim; Muhdiana, Dedi; Aji, Prima Trisna; Kurniati, Dede; Sudrajat, Diwa Agus (Open Access Macedonian Journal of Medical Sciences, 2021)
BACKGROUND: COVID-19 pandemic has developed into a major public health threat. Nurses who work to combat COVID-19 are frequently under pressure. The high stresses caused by the consequences of transmission of the COVID-19 put nurses at risk of developing burnout syndrome. AIM: The purpose of this study was to evaluate the level of anxiety and burnout experienced by nurses during the COVID-19 pandemic. METHODS: This study was conducted using a cross-sectional design. An online web-based survey was used to collected data in the national sample of nurses (n = 243, response rate = 78.6%). This study used a convenience sampling technique. The Hamilton Anxiety Rating Scale and the Maslach Burnout Inventory were also employed. Multiple linear regressions were used to determine characteristics associated with burnout. RESULTS: The participants’ average age was 34.62 years (SD = 7.91). The mean anxiety score was 7.89 (SD = 2.94). The mean score of emotional exhaustion was 14.35 (SD = 7.72), the depersonalization means score was 8.81 (SD = 5.11), and the professional accomplishment mean score was 13.51 (SD = 7.51). Education and job experience had a substantial effect on emotional exhaustion and depersonalization, with R2 values of 10.8% and 18.5%, respectively. When anxiety was included in the model, the R2 for emotional exhaustion increased to 20.4% and the R2 for depersonalization increased to 22.2%, respectively. Work experience had a little effect on professional accomplishment (R2 = 10.3%) but had a much larger effect when the variable of anxiety was included in the model (R2 = 18.3%). CONCLUSION: This study revealed that during the COVID-19 epidemic, nurses experienced many emotional states, including exhaustion, depersonalization, and anxiety. Efforts should be made by governments and policymakers in this regard in better preparing health-care systems, persons, and nursing to respond to the COVID-19 pandemic in the future.